Utilization of Nanotechnology to Improve Bone Health in Osteoporosis Exploiting Nigella sativa and Its Active Constituent Thymoquinone - Javed Ahmad; Hassan A. Albarqi; Mohammad Zaki Ahmad; Mohamed A. A. Orabi; Shadab Md; Ritam Bandopadhyay; Faraha Ahmed; Mohammad Ahmed Khan; Javed Ahamad; Awanish Mishra (Bioengineering, 2022)
Osteoporosis, a chronic bone disorder, is one of the leading causes of fracture and morbidity risk. Numerous medicinally important herbs have been evaluated for their efficacy in improving bone mass density in exhaustive preclinical and limited clinical studies. Nigella sativa L. has been used as local folk medicine, and traditional healers have used it to manage various ailments. Its reported beneficial effects include controlling bone and joint diseases. The present manuscript aimed to provide a sound discussion on the pharmacological evidence of N. sativa and its active constituent, thymoquinone, for its utility in the effective management of osteoporosis. N. sativa is reported to possess anti-IL-1 and anti-TNF-α-mediated anti-inflammatory effects, leading to positive effects on bone turnover markers, such as alkaline phosphatase and tartrate-resistant acid phosphatase. It is reported to stimulate bone regeneration by prompting osteoblast proliferation, ossification, and decreasing osteoclast cells. Thymoquinone from N. sativa has exhibited an antioxidant effect on bone tissue by reducing the FeNTA-induced oxidative stress. The present manuscript highlights phytochemistry, pharmacological effect, and the important mechanistic perspective of N. sativa and its active constituents for the management of osteoporosis. Further, it also provides sound discussion on the utilization of a nanotechnology-mediated drug delivery approach as a promising strategy to improve the therapeutic performance of N. sativa and its active constituent, thymoquinone, in the effective management of osteoporosis.